11 and 15-month-old infants do not compensate immediately for energy variation, and no further adjustment occurs 12 or 24 hours later. (1st July 2021) - Brugaillères, Pauline; Issanchou, Sylvie; Chabanet, Claire; Marty, Sylvie; Schwartz, Camille
Abstract: Previously, we demonstrated that, in the short term, infants undercompensated for the energy from a preload given 25 min before an ad libitum meal. However, although not consistent, there is evidence in young children that caloric adjustment may occur over longer periods. We investigated the extent to which further energy adjustment occurs up to 24 h after a single meal preceded by preloads of varying energy density (ED) in infants that are 11 and 15 months old. Short-term caloric adjustment was measured in 11- and 15-month-old infants through a preload paradigm meal in the laboratory. To assess their caloric adjustment over longer periods (12 and 24 h), we used 24 h dietary records to evaluate the energy intake (EI) after each visit to the laboratory. Three COMPX scores were calculated according to three different time periods after preload consumption (0 h [i.e., short-term], 12 h or 24 h). Our main result was that, on average, regardless of the time period considered, the infants undercompensated their EI after preload consumption: at 11 and 15 months, caloric adjustment was partial and similar overtime. Considering that a slight repeated imbalance of the energy balance may promote rapid weight gain over the first months, this study calls for further research focusing on facilitators and barriers of efficient appetite control abilities in infancy.